Swiftlet Bird's Nest (Collocalia fuciphaga) from West Sumatra as a Functional Food and Its Nutritional Content - Aditya Willy Putra; Endang Purwati; Marlina (Andalasian Livestock, 2024)
Functional foods contain biologically active components and compounds that have physiological effects on the human body, such as promoting health and decreasing the risk of sickness. The swiftlet, which belongs to the Collocalini family, is an insect-eating bird that migrates across the Indian Ocean, Southeast Asia, and northern Australia to the Pacific Ocean. Swiftlet bird's nests (SBN) contain protein, fats, carbohydrates, iron, calcium, phosphorus, inorganic salts, fiber, and water. The objective of this study is to determine the nutritional content of swiftlet bird nests in different regions of West Sumatra. Samples of swiftlet bird's nests (SBN) were collected from Padang City (PD), Bukittinggi City (BK), and Pesisir Selatan Regency (PS). Nutritional content was analyzed using proximate methods, including moisture, protein, and fat, and the nitrite concentration was measured using UV-Vis spectrophotometry. The study found that SBN in West Sumatra contains 47.65–50.55% protein, 1.48–2.47% fat, 21.77–22.77% water, and 24.75–32.72 ppm nitrite. The results indicate that the nutritional content varies among the samples, and the protein content found in SBN is higher, making it suitable for use as a functional food. Additionally, SBN has many health benefits and biological activities, such as mitogenic response and cell growth, enhanced immunity, and improved bone strength.